Gas Transfer between the Inner 3 kpc Disk and the Galactic Central Molecular Zone - Yang Su; Shiyu Zhang; Yan Sun; Ji Yang; Fujun Du; Min Fang; Qing-Zeng Yan; Shaobo Zhang; Zhiwei Chen; Xuepeng Chen; Xin Zhou; Lixia Yuan; et al. (The Astrophysical Journal)
We uncovered a more tilted molecular gas structure with highly negative velocities located near the dust lane. Our observations show that the approaching gas flows from the overshoot process are captured by the gravitational potential of the bar and then flow toward the Galactic central molecular zone (CMZ) through the bar channel. The recycled gas from the overshoot effect, in conjunction with freshly accreted gas from the inner 3 kpc disk, accumulates significantly near the ${R}_{{\rm{GC}}}\sim \frac{1}{2}{R}_{{\rm{bar}}}$ and ${R}_{{\rm{GC}}}\sim \frac{2}{3}{R}_{{\rm{bar}}}$ regions by adopting a bar length of ∼3.2–3.4 kpc. Importantly, within these regions, there are frequent collisions and substantial angular momentum exchanges between gas flows with different trajectories. In this scenario, the dissipation processes arising from interactions between colliding flows, together with the varying torques induced by the nonaxisymmetric bar, effectively transfer the angular momentum of viscous gas outward, thereby driving the molecular gas to settle into the CMZ within about three orbital periods. A long-term gas inflow with an average rate of ≳1.1 M _⊙ yr ^−1 , coupled with intense transient accretion events that exceed the average rate by several times due to the overshoot effect, significantly regulates the gas distribution, physical properties, and dynamical evolution of the CMZ. These new findings provide robust observational evidence for elucidating the intricate dynamics of molecular gas flows toward the CMZ. Our observations suggest that gas dynamics have a significant impact on the secular evolution of both the Milky Way and the extragalactic gas-rich galaxies.